Determination of the Energetic Value of Corn, Soybean Meal and Micronized Full Fat Soybean for Newly Hatched Chicks - FA Longo (Revista Brasileira de Ciência Avícola, 2004)
There are some evidences described in the literature showing reduced energy metabolizability of ingredients for newly hatched chicks. Hence, a metabolism trial was carried out with the objective of determining the metabolizable energy of corn grain, soybean meal and micronized full fat soybean for newly hatched chicks. The method of total excreta collection was used in an experiment with 192 male chicks from one to seven days, distributed in a completely randomized design with four treatments and four replicates of twelve birds. Excreta were collected from four to seven days of age. The treatments included a reference diet, two test-diets consisting of 60% of the reference diet and 40% of the test ingredients: corn grain (CG) and soybean meal (SM), and one test-diet consisting of 80% of the reference diet and 20% of micronized full fat soybean (MFFS). The N-corrected apparent metabolizable energy (AMEn) and the metabolizability coefficient of gross energy (MCGE) of the ingredients determined for the chicks were respectively 3,213 kcal/kg and 81.6% for CG; 2,085 kcal/kg and 49.7% for SM and 4,068 kcal/kg and 74.8% for MFFS.